IMPLEMENTASI COST PLUS PRICING PENDEKATAN FULL COSTING PENENTU HARGA JUAL PADA PABRIK MEKAR JAYA - Septiani, Erika Tri; Nurdiwaty, Diah; Kurniawan, Andy (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
P This study aims to analyze how to calculate the cost of production through the full costing approach and determine the selling price of the desert Krecek using the cost plus pricing method compared to that based on the Mekar Jaya Krecek Factory method. This research is a descriptive type of research using a quantitative approach. Data were obtained through field studies (interviews, observation, and documentation), literature studies, and internet research. In this study, quantitative descriptive analysis is the data analysis method used. The results show that there is a difference in the calculation of the selling price, with the Mekar Jaya Krecek factory method the selling price is lower than the cost plus pricing method with the full costing approach. For white krecek the price difference is Rp. 1,142, and Rp. 1225 for outside red krecek. Thus, the calculation using the cost plus pricing method of the full costing approach can be used as a material consideration by the Mekar Jaya Krecek Factory in deciding the selling price of its products.